Nigerian produce marketing company limited: Functions and organisation - Nigerian produce marketing company limited (Lagos Nigerian Produce Marketing Company , Limited, 1967)
This book provides the organisational structure of the Nigerian produce marketing company including the composition and the objectives that step up the institute.
asm; 06/03/19
Loans
Keywords: Agriculture-Economic aspects; produce--Marketing; Nigeria